High‐Throughput Single‐Nucleus RNA Profiling of Minimal Puncture FFPE Samples Reveals Spatiotemporal Heterogeneity of Cancer - Weiqin Jiang; Xiang Zhang; Ziye Xu; Qing Cheng; Xiaohan Li; Yuyi Zhu; Fangru Lu; Ling Dong; Linghui Zeng; Weixiang Zhong; Yongcheng Wang; Longjiang Fan; et al. (Advanced Science)
Abstract Puncture biopsy, especially those preserved by formalin fixed paraffin embedding (FFPE) samples, play an important role in various research purposes. Diverse single‐nucleus RNA sequencing (snRNA‐seq) techniques have been developed for FFPE samples, however, how to perform high‐throughput snRNA‐seq on small FFPE puncture samples is still a challenge. Here, the previously developed snRNA‐seq technique (snRandom‐seq) is optimized by implementing a pre‐indexing procedure for the minimal puncture FFPE samples. In analyzing 20 samples from various solid tumors, optimized snRandom‐seq still detected ≈17 000 genes and 12 000 long non‐coding RNAs (lncRNAs), achieving precise clustering based on tissue origin. A head‐to‐head comparison with 10× Genomics on fresh biopsy samples showed a similar gene detection rate, with significantly enhanced lncRNA detection, indicating that the optimized snRandom‐seq technique maintains its established gene detection advantages even when applied to small samples. Utilizing 7 puncture FFPE samples of liver metastases from 3 colorectal cancer patients pre‐ and post‐immunotherapy, the cellular developmental trajectories are reconstructed and revealed dynamic spatiotemporal heterogeneity during treatment, including insights into pseudoprogression of immunotherapy. Therefore, the optimized snRandom‐seq offers a solution for high‐throughput single‐cell RNA and non‐coding RNA analysis in minimal puncture FFPE sample.